Globalizing Local Policing: An Ethnography of Change and Concern Among Danish Detectives - Sausdal, David (Transnational Crime, Crime Control and Security, 2023)
1. Introduction -- 2. Xenophobia -- 3. Orwellianism -- 4. Terrorism -- 5. Cynicism -- 6. Politics -- 7. Nostalgia -- 8. Conclusion: A policing puzzle.